Comparative transcriptome analyses reveal the genetic basis underlying the immune function of three amphibians’ skin - Fan, Wenqiao; Jiang, Yusong; Zhang, Meixia; Yang, Donglin; Chen, Zhongzhu; Sun, Hanchang; Lan, Xuelian; Yan, Fan; Xu, Jingming; Yuan, Wanan (PLOS ONE, 2017)
Skin as the first barrier against external invasions plays an essential role for the survival of amphibians on land. Understanding the genetic basis of skin function is significant in revealing the mechanisms underlying immunity of amphibians. In this study, we de novo sequenced and comparatively analyzed skin transcriptomes from three different amphibian species, Andrias davidianus, Bufo gargarizans, and Rana nigromaculata Hallowell. Functional classification of unigenes in each amphibian showed high accordance, with the most represented GO terms and KEGG pathways related to basic biological processes, such as binding and metabolism and immune system. As for the unigenes, GO and KEGG distributions of conserved orthologs in each species were similar, with the predominantly enriched pathways including RNA polymerase, nucleotide metabolism, and defense. The positively selected orthologs in each amphibian were also similar, which were primarily involved in stimulus response, cell metabolic, membrane, and catalytic activity. Furthermore, a total of 50 antimicrobial peptides from 26 different categories were identified in the three amphibians, and one of these showed high efficiency in inhibiting the growth of different bacteria. Our understanding of innate immune function of amphibian skin has increased basis on the immune-related unigenes, pathways, and antimicrobial peptides in amphibians.